Working Through Colonial Collections An Ethnography of the Ethnological Museum in Berlin - von Oswald, Margareta (Leuven University Press, 2022)
Reckoning with colonial legacies in Western museum collections What are the possibilities and limits of engaging with colonialism in ethnological museums? This book addresses this question from within the Africa department of the Ethnological Museum in Berlin. It captures the Museum at a moment of substantial transformation, as it prepared the move of its exhibition to the Humboldt Forum, a newly built and contested cultural centre on Berlin's Museum Island. The book discusses almost a decade of debate in which German colonialism was negotiated, and further recognised, through conflicts over colonial museum collections. Based on two years of ethnographic fieldwork examining the Museum's various work practices, this book highlights the Museum's embeddedness in colonial logics and shows how these unfold in the Museum's everyday activity. It addresses the diverse areas of expertise in the Ethnological Museum - the preservation, storage, curation, and research of collections - and also draws on archival research and oral history interviews with current and former employees. Working through Colonial Collections unravels the ongoing and laborious processes of reckoning with colonialism in the Ethnological Museum's present - processes from which other ethnological museums, as well as Western museums more generally, can learn. With a preface by Sharon Macdonald. Ebook available in Open Access. This publication is GPRC-labeled (Guaranteed Peer-Reviewed Content).